Sensory Workpieces for Process Monitoring – An Approach. (2016) - Denkena, B.; Dahlmann, D.; Boujnah, H.
Abstract: Several research projects deal with the development of sensory machine components for process monitoring. Especially those components, which are closely located to the process, show acceptable sensitivities to process loads and are therefore convenient for sensor integration. Considering that workpieces represent the focus of each manufacturing process and the origin of acting force and heat fluxes, they offer a "higher quality" information source for mechanical and especially thermal process loads. The development of sensory workpieces allows novel process monitoring strategies. It leads, however, to totally different challenges concerning sensor placement, energy and data transmission. So far sensory workpieces have been subject to little research. This paper focuses on the vision and the actual developments of sensory workpieces for milling operations. First, the technical challenges are identified and concepts to meet the function requirements are introduced. Then, a simulation-based approach for the placement of strain sensors in workpieces to detect the mechanical load while machining is discussed in details. Finally, the design of signal devices and the data communication by a sensor network for process monitoring tasks are presented.